The fate of glyphosate and AMPA in a freshwater endorheic basin: An ecotoxicological risk assessment - Bonansea, Rocío Inés (2017)
Glyphosate is themostwidely used herbicideworldwide. However, there are some uncertain aspects with respect to its environmental fate. To evaluate the existence and distribution of this pesticide and its metabolite, aminomethylphosphonic acid (AMPA), their presence in fresh water, sediment, and suspended particulate matter (SPM) was measured in samples collected in a river running across a large city and through areas with intensive and extensive agriculture. The aquatic risk associated to the occurrence of these compounds was estimated using the hazard quotient (HQ) calculation for water and sediment. From the analyzed samples, overall 35% contained glyphosate, AMPA, or both compounds. Concentrations of the analytes were spread in different percentages depending on the environmentalmatrices considered,with levels ranging from12 to 20 times higher for glyphosate and AMPA in sediment and SPM, as compared with the levels found in water. The most polluted area was situated within a green belt zone of the city; while in second place were sites located in areas of extensive agriculture. Aquatic organisms inhabiting areas both inside and outside agricultural areas are threatened by water glyphosate concentrations. Benthic organisms inside the greenbelt zone and inside the lower basin are threatened by the concentrations of glyphosate in sediment. Even when the concentrations measured in water were below the levels of concern for wildlife, results showed the risk of agricultural practices to aquatic biota. An update of the limits established for freshwater biota protection is needed.